Realistic Mathematics Education for 21st Century Skills: Strengthening Collaboration and Critical Thinking in Mathematics Learning - Febriana, Rina; Delyana, Hafizah; Cesaria, Anna; Sovia, Anny (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2026)
The development of 21st-century skills, particularly collaboration and critical thinking, has become a central objective in contemporary mathematics education. The Realistic Mathematics Education (RME) approach is considered a promising intellectual strategy for supporting these competencies through contextual problem-solving activities and structured social interactions. However, emperiecal evidence on the simultaneous contribution on both critical thinking and collaborative skills remains limited. This study aims to assess the effect of the RME approach on students’ critical thinking and collaborative skill in mathematics learning. A quantitative approach using a quasi-experimental pretest–posttest control group design involving sixty students, divided into an experimental group receiving RME instruction (n = 30) and a control group receiving conventional instruction (n = 30). The research instruments included a critical thinking skills test and an observation-based collaboration skills assessment. Data were analyzed using Multivariate analysis of Covariance to assess the combined effects of RME while controlling for initial abilities .The results revealed that the experimental group ashowed significantly higher posttest scores in critical thinking skills (M = 82.15) compored to the control group (M = 70.46), with N-Gain scores of 0.61 and 0.35, respectively. Similarly, students’ collaborative skills in the experimental group (M = 84.27) were higher than those in the control group (M = 71.15). Multivariate analysis confirmed a statistically significant effect of RME on both critical thinking and collaboration. These findings suggest that RME effectively enhances students' cognitive and social competencies and can serve as an alternative strategy for mathematics instruction.